Identification of Indigenous Bacteria from Dumai Sea Waters Using 16S rRNA Method - Fatwa, Esa Buana; Yoswaty, Dessy; Effendi, Irwan (Journal of Coastal and Ocean Sciences, 2021)
Indigenous bacteria are bacteria that naturally live freely in nature and have a variety of benefits for humans. These bacteria also have the potential to degrade pollution bacteria in the water. This research was conducted in November-December 2020. The purpose of this study was to and identify indigenous bacteria from dumai sea waters using the PCR method of 16S rRNA sequence technique. Based on the results of the study based on the analysis of 16S rRNA it is known that isolate 10 belongs to the bacterium genus Bacillus and has a homological rate of 93% with Bacillus paramycoides bacteria. Based on the phylogenic tree of isolate bacteria 10 does not have nodes associated with ten bacteria contained in NCBI. This suggests that phylogenically indigenous bacteria ISL 10 have no species similarity to the ten bacterial isolates in the phylogenetic tree, but have a similarity of base order of 93% to B. paramycoides